2002
DOI: 10.1086/342404
|View full text |Cite
|
Sign up to set email alerts
|

The Enrichment History of the Intergalactic Medium: Oviin Lyα Forest Systems at Redshiftz ∼ 2

Abstract: A search for O vi 1031.93, 1037.62 Å at redshifts corresponding to Ly lines in the z em $ 2:4 QSOs HE 1122À1648 and HE 2217À2818 reveals that a substantial fraction of those with H i column densities log NðH iÞ > 14:0 (cm À2 ) are highly ionized and show some heavy-element enrichment. If these two sight lines are typical, then the O vi systems contain a cosmologically significant fraction of the baryons and the metals in the universe. For most systems the temperatures derived from the line widths are too low f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(156 citation statements)
references
References 23 publications
14
140
2
Order By: Relevance
“…In order to obtain the absorption line parameters (the redshift z, the column density N in cm −2 and the Doppler parameter b in km s −1 ), we have performed a Voigt profile fitting analysis using VPFIT 1 . Details can be found in the documentation provided with the software, Carswell, Schaye & Kim (2002) and Kim et al (2007). Here, we only give a brief description of the fitting procedure.…”
Section: Data and Voigt Profile Fittingmentioning
confidence: 99%
“…In order to obtain the absorption line parameters (the redshift z, the column density N in cm −2 and the Doppler parameter b in km s −1 ), we have performed a Voigt profile fitting analysis using VPFIT 1 . Details can be found in the documentation provided with the software, Carswell, Schaye & Kim (2002) and Kim et al (2007). Here, we only give a brief description of the fitting procedure.…”
Section: Data and Voigt Profile Fittingmentioning
confidence: 99%
“…Because O vi is placed within the Ly , Ly , and higher order Lyman forests, our first step has been to follow the procedure of Carswell et al (2002), fitting the entire Ly forest region to remove high-order H i transitions from the data. Beginning at the emission redshift of the quasar, each H i line in the forest was fitted with a combination of Voigt profiles using the VPFIT 6 software package.…”
Section: Identification and Measurement Of The O VI Systemsmentioning
confidence: 99%
“…However, Schaye et al (2000) have claimed a detection of O vi even at very low densities, reaching below the cosmic mean. More recently Carswell, Schaye, & Kim (2002) and Bergeron et al (2002) have discovered evidence for O vi enrichment in a number of individual systems with N H i $ 10 14:5 at z $ 2:3. This paper expands upon these studies by using an increased number of sight lines observed at high resolution and also by incorporating the full use of nondetections in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a simple picture where O vi and C iv arise from spatially distinct volumes one would expect to find O vi shifted statistically to higher as well as lower velocities. Checking the O vi selected systems reported by Carswell et al (2002) and Simcoe et al (2002), O vi features at high redshift seem to be shifted to positive velocities with respect to C iv if they are displaced at all. At low redshift Tripp et al (2008) have recently found a displacement between H i and O vi in particular for complex O vi systems.…”
Section: Comparison To C Ivmentioning
confidence: 88%